MECHANICS OF A ROCK BODY WITH BLOCK STRUCTURE - Sadovskiy M.A.; Kocharyan G.G.; Rodionov V.N. (My University, 1988)
We consider the movement of free blocks in a rock body undergoing deformation. To identify the principal qualitative phenomena accompanying this process, a simple model is used. A cubic block interacts with neighboring blocks. Force is transmitted only to faces that are lateral in the direction of movement of the block, and no forces opposing this movement act on the end faces. Assuming that the velocity of transverse elastic waves in the partings between blocks is an order of magnitude smaller than in the block itself, we can estimate the characteristic oscillation frequency of a free block in the body.